UNJUK KERJA VOICE OVER INTERNET PROTOCOL PADA JARINGAN LOKAL UNIVERSITAS JENDERAL SOEDIRMAN - Alfa Pradipta; Azis Wisnu Widhi Nugraha; Iwan Setiawan (Dinamika Rekayasa, 2012)
Jenderal Soedirman University (UNSOED) LAN covers all of its units that spread not only in Purwokerto area, but also in Purbalingga. Therefore, it may be possible to implement VoIP system in order to replace the internal campus voice telecommunication system that still use PSTN and PABX (line extensions). The Implementation of VoIP technology into UNSOED LAN needs a VoIP server prototype to be built for quality testing. VoIP quality of service (QoS) is based on delay, jitter, and packet loss. These parameters will be used as QoS test parameters in this research. We also add subjective test runs by users to measure the voice quality of VoIP. According to Ridwan (2011), the optimum codec that can be applied in UNSOED LAN is iLBC. Our research result shows that the highest mean for delay, jitter, packet loss respectively are 3 milliseconds, 19,333 milliseconds, 1%, and the voice quality is good . These indicated that the VoIP QoS and voice quality on UNSOED LAN is in a good category.